Data inputs and assumptions in calculating the fatal burden in burden of disease studies. (30th September 2020) - von der Lippe, E; Grant, I; Devleesschauwer, B
Abstract: Years of Life Lost (YLL) is a measure of premature mortality used in the calculation of the Disability-Adjusted Life Year (DALY), as well as stand-alone measure in itself. The concept of years of life lost is to estimate the length of time a person is expected to have lived had they not died prematurely. The YLL is based on comparing the age of death to an external standard life expectancy curve, and can incorporate time discounting and age weighting. Furthermore, YLL can be calculated for specific causes of death. In this way the indicator can be used to compare the relative importance of different causes of premature death within a particular population. Thus, it can be used by health planners to define priorities for the prevention interventions. The process of calculating a YLL involves several components and this presentation will provide a sequential walk through each step in the YLL calculation, including causes of death statistics definition of ill-defined deaths methods of redistribution of ill-defined deaths the use of life tables social weighting The aim of this presentation is to outline a simple step by step guide on the key components in the YLL calculation. Using the real-life example of cerebrovascular disease, the presentation will outline the key choices and assumptions that underline each data inputs in the YLL calculation. Participants in this session will also be provided with links to resources to help facilitate this decision making process. The workshop will end with an interactive session where the presenters will discuss the implications of the different methodological choices with the audience.